P-8 Pre implementation evaluation of advance care plans at st vincent's prior to organisational implementation of the bestcare ACP program pilot in. (1st September 2015) - Boughey, M; Scott, C; Barker, N; Langham, R
Abstract : Background: The determination of a preferred course of care presents patients with chronic disease, their carers and clinicians with difficult choices. Advance Care Plans (ACP) document patients wishes and goals of care so these are respected even when capacity is diminished. The best CARE ACP pilot will initiate planning and provide compassionate support during the process in alignment with the Mission of St Vincent's Melbourne (SVHM). Aim: To evaluate the use of ACPs and staff and patient understanding and attitudes to them in the SVHM dialysis unit prior to the implementation of the best CARE ACP pilot program. Methods: An audit of ACP documents at SVHM was undertaken and dialysis staff and patient understanding and attitudes to ACPs were surveyed. Results: 43 patients had an ACP in the patient records for the period 2012–2014. Mean patient age was 70 and 28 (65%) were female. 28 (65%) of the plans were made by Jehovah's Witnesses. No dialysis patients had an ACP. 31 staff and 20 patients were surveyed. Dialysis staff thought that ACPs were important and felt that lack of patient knowledge was a major problem. 70% of patients had no or little knowledge of ACPs but 80% thought they were important for care. Perceived benefits included ability to express wishes (84%) and reducing the burden for family (68%). 58% thought they should have an ACP. Discussion/conclusion: Evaluation of Advance Care Plans pre implementation of the organisational ACP program demonstrated that plans were infrequently utilised and the majority relate to a specific patient group. Attitudes amongst staff and patients were largely positive but patient knowledge was poor.